The distribution of tuberculosis in Porto Alegre: analysis of the magnitude and tuberculosis-HIV coinfection - Rarianne Carvalho Peruhype; Lisiane Morelia Weide Acosta; Antônio Ruffino Netto; Mônica Maria Celestina de Oliveira; Pedro Fredemir Palha
Objective Analyzing the geographical distribution of the tuberculosis (TB), its incidence and prevalence and TB-HIV coinfection in the districts of Porto Alegre from 2007 to 2011. Method An ecological, descriptive study of time series that used descriptive and geoprocessing techniques. Results In total, were recorded 3,369 incident cases and 3,998 prevalent cases of pulmonary TB. In both contexts, there was predominance of cases in males and in Caucasians. Seventeen districts showed prevalence rates above 79.2 cases/100,000 inhabitants, considering that 15 of them had incidence rates above 73.7 cases/100,000 inhabitants. The TB-HIV coinfection rates reached 67% in some districts, which is above the city average value (30%). Conclusion The distribution analysis showed that the reformulation and restructuring of policies and health services in Porto Alegre are essential.